Evidence-based nutrition and clinical evidence of bioactive foods in human health and disease - Duttaroy, Asim K. (Academic Press, 2021)
Evidence-Based Nutrition and Clinical Evidence of Bioactive Foods in Human Health and Disease explores a wide range of studies from clinical investigations to mechanistic research, covering the actions of bioactives on specific tissues and cells in intestinal, neurological, immunological and cardiovascular health and disease, including cancers. The book also focuses on metabolism, mechanisms of actions, tissue-specific effects, and the structure-function relationships between clinical trial, ex vivo and in vitro data. Written for nutrition researchers, clinical researchers, dieticians, and others working in and studying health-related fields, this book highlights the concepts surrounding the preventive and therapeutic impacts of bioactive foods.